Sistem Pendukung Keputusan untuk Menentukan Kelayakan Siswa Penerima Bantuan Pendidikan dengan Metode SMART Berbasis Website - Lisda Pebriyanti; Ahmad Fauzi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Determining the eligibility of students to receive educational assistance is an essential process that requires accurate, objective, and systematic evaluation. At SD Negeri Tipar, the selection process is still conducted manually through conventional assessment and administrative checking, which often leads to inefficiency, data inconsistencies, and difficulties in determining fair and accountable decisions. To address these challenges, a web-based Decision Support System was developed using the Simple Multi-Attribute Rating Technique (SMART) method. This system evaluates students based on several social-related criteria, including parental income, parental occupation, number of dependents, housing ownership, and access to educational facilities. Each criterion is weighted according to its level of importance, and the final eligibility score is computed automatically using the SMART calculation stage. The results of system implementation show that the application can accurately generate ranking recommendations for student eligibility and provide structured reports to support transparent decision-making. This system enhances the effectiveness, accuracy, and fairness of the aid distribution process while helping schools ensure that assistance is allocated to student who need it most.